Hubungan Self Efficacy dan Kemampuan Pemecahan Masalah Siswa pada Materi Trigonometri - Islamiati, Ayu Diah; Suratman, Dede; Dona Fitriawan (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
The purpose of this study was to determine the relationship between high school students' self-efficacy and their ability to solve trigonometric problems. This research is an example of ex post facto correlational research developed using quantitative methodology. All research participants were students of class XG SMA Negeri 8 Pontianak. The method included administering a self-efficacy test and an essay-based assessment of one's ability to solve mathematical problems. The results showed that students' self-efficacy and math problem solving ability were in the moderate range. To determine the relationship between the two variables, data analysis was conducted. The data showed linear correlation and normal distribution. The Pearson Product Moment test was then used to conduct the correlation analysis. The test result is Sig.(2-tailed) < a or 0.034 < 0.05 As a result, it can be said that self-efficacy and math problem-solving aptitude are related. In other words, as students improve in solving math challenges, their self-efficacy will grow.